TRIM5α Resistance Escape Mutations in the Capsid Are Transferable between Simian Immunodeficiency Virus Strains - Wu, Fan (J Virol, 2016)
TRIM5α polymorphism limits and complicates the use of simian immunodeficiency virus (SIV) for evaluation of human immunodeficiency virus (HIV) vaccine strategies in rhesus macaques. We previously reported that the TRIM5α-sensitive SIV from sooty mangabeys (SIVsm) clone SIVsmE543-3 acquired amino acid substitutions in the capsid that overcame TRIM5α restriction when it was passaged in rhesus macaques expressing restrictive TRIM5α alleles. Here we generated TRIM5α-resistant clones of the related SIVsmE660 strain without animal passage by introducing the same amino acid capsid substitutions. We evaluated one of the variants in rhesus macaques expressing permissive and restrictive TRIM5α alleles. The SIVsmE660 variant infected and replicated in macaques with restrictive TRIM5α genotypes as efficiently as in macaques with permissive TRIM5α genotypes. These results demonstrated that mutations in the SIV capsid can confer SIV resistance to TRIM5α restriction without animal passage, suggesting an applicable method to generate more diverse SIV strains for HIV vaccine studies. IMPORTANCE Many strains of SIV from sooty mangabey monkeys are susceptible to resistance by common rhesus macaque TRIM5α alleles and result in reduced virus acquisition and replication in macaques that express these restrictive alleles. We previously observed that spontaneous variations in the capsid gene were associated with improved replication in macaques, and the introduction of two amino acid changes in the capsid transfers this improved replication to the parent clone. In the present study, we introduced these mutations into a related but distinct strain of SIV that is commonly used for challenge studies for vaccine trials. These mutations also improved the replication of this strain in macaques with the restrictive TRIM5α genotype and thus will eliminate the confounding effects of TRIM5α in vaccine studies.